Dampak Festival Budaya Pertanian terhadap Kawasan Pertanian Di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - DEWI, IDA AYU GDE PURNA; WINDIA, I WAYAN; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Impact of the Agricultural Culture Festival on the Agricultural Area in Pelaga Village, Petang District, Badung Regency Agricultural Culture Festival in Pelaga Village, Petang District, Badung Regency is initiated to improve the image of agriculture, agritourism, nature conservation, creative economy, agricultural product transaction, and agricultural synergy. The purpose of the event is to increase tourist visits, product marketing, and the regional income of Badung Regency. This research aims to analyze the impact of the Agricultural Culture Festival on tourism image improvement in the North Badung region. This study uses qualitative methods. Primary data was collected through in-depth interviews with key informants and secondary data was obtained from literature in the form of books, journals, book reviews, online mass media, and other sources. The results showed that the implementation of the Agricultural Culture Festival on agricultural areas in Pelaga Village, Petang District, Badung Regency has a positive impact on the image of agriculture as a tourist attraction, agro-tourism development, nature conservation, creative economy, agricultural product transactions, and agricultural synergy. Suggestions from this research are that the Agricultural Culture Festival activities will further develop or add innovations so that people remain enthusiastic about participating in these activities and provide wider opportunities for local people in agricultural cultural festival activities. The agriculture and food office is expected to be able to add new activities to the implementation of agricultural cultural festivals with innovations such as coffee stands featuring local baristas, the election of Jegeg Bagus ambassadors, optimizing the role of the Women's Farmers Group and the local community, optimizing the role of students and creating young people as educational media. and investment. The existence of an increase in innovation activities at the implementation of agricultural culture festivals can develop and continue to be implemented. The continued implementation of these activities and the development of innovations are expected to increase the enthusiasm of the community, especially the Pelaga Village farmers in participating in these activities.